The relationship between knowledge about the pandemic and willingness to get vaccinated against SARS-CoV-2 in medical students in Poland: A cross-sectional survey - Jastrzẹbska, Aleksandra; Saden, Gabrielle; Knysz, Brygida; Pondel, Maciej; Siennicka, Agnieszka (Frontiers in Public Health, 2022)
The COVID-19 pandemic underlines the cruciality of targeting the groups with the highest risk of vaccine hesitancy, understanding their fears and alleviating them. As the pandemic situation is very dynamic due to the appearance of new SARS-CoV-2 variants, concerns might also change over time. This is the first study to evaluate the vaccination rate and state of knowledge among medical students in Poland, comparing English and Polish divisions. We collected the data in a two-month period. A total of 1521 surveys were collected: 273 students from the English division and 1248 students from the Polish division answered the survey. The questionnaire was aimed at investigating students’ awareness, knowledge and apprehensions towards the COVID-19 pandemic and vaccines. The results were obtained for the following statements: good knowledge about ways of transmission is not statistically significant in determining if a student is vaccinated. Moreover, a year of studies is not statistically significant in determining if a student knows all ways of COVID-19 transmission. Interestingly the correlation between the statement "Keeping up to date with the upcoming vaccines is important for my role as a future health care worker" and being vaccinated against SARS-CoV-2 showed that 45.5% of unvaccinated students did not update their information about the vaccines and rated 1 out of 5 to this statement (p<0.001). Even though the pandemic will not last forever the obtained knowledge about the role of individual interests’ can be applied in many different life situations as this feature is statistically significant.